Vaporization of metallic macroparticles in the high temperature technology plasma - Bizyukov, A.A.; Chibisov, A.D.; Romashchenko, E.V.; Kolyada, Yu.E. (Вопросы атомной науки и техники, 2016)
The possibility of evaporation of macroparticles (MP) in collisionless plasma as a result of MP heating due to collisions with the plasma particles is studied. The problem of determining the self-consistent values of stationary MP temperature and its potential as a function of the plasma number density and the electron temperature is solved. The time of complete evaporation of the MP is calculated. Parameters of the MP which can be evaporated during the passage through the region of heated plasma are determined. Degree of ionization of the evaporated atoms of the MP substance is evaluated.